2000
DOI: 10.1007/s100500050425
|View full text |Cite
|
Sign up to set email alerts
|

The Nambu–Jona–Lasinio model of light nuclei

Abstract: The Nambu-Jona-Lasinio model of the deuteron suggested by Nambu and Jona-Lasinio (Phys. Rev. 124 (1961) 246) is formulated from the first principles of QCD. The deuteron appears as a neutronproton collective excitation, i.e. a Cooper np-pair, induced by a phenomenological local four-nucleon interaction in the nuclear phase of QCD. The model describes the deuteron coupled to itself, nucleons and other particles through one-nucleon loop exchanges providing a minimal transfer of nucleon flavours from initial to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(40 citation statements)
references
References 28 publications
(161 reference statements)
1
39
0
Order By: Relevance
“…we evaluate at leading order in the large N C expansion [1]. The results of the evaluation contain divergent contributions.…”
Section: Chiral One-meson Loop Corrections To the Amplitude Of The M1mentioning
confidence: 99%
See 4 more Smart Citations
“…we evaluate at leading order in the large N C expansion [1]. The results of the evaluation contain divergent contributions.…”
Section: Chiral One-meson Loop Corrections To the Amplitude Of The M1mentioning
confidence: 99%
“…We have shown that the NNJL model is fully motivated by QCD [1]. The deuteron appears in the nuclear phase of QCD as a neutron-proton collective excitation, a Cooper np-pair, caused by a phenomenological local four-nucleon interaction.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations